Game Theory as A Method of Analysis of Visits to Yasukuni Shrine by Japanese Prime Ministers: Case Study Based on Jun’ichirō Koizumi’s Visits - Pletnia, Maciej (Rethinking Asia in World Politics, 2023)
This paper aims to use game theory to analyze the decision-making process associated with Japanese prime ministers’ visits to the Yasukuni shrine. The central thesis of the research is that it is possible to construct a model that enables the analysis of past visits to the shrine and assess the probability of such visits in the future. The presented research is a case study based on Jun’ichirō Koizumi’s visits during his term as Prime Minister of Japan. The model used for the analysis is based on the ‘chicken dilemma’ and is an example of a non-cooperative and repeated game. Relying on the model also allows us to juxtapose foreign pressures with those exerted by domestic interest groups, as preliminary findings suggest that using game theory to analyze visits to Yasukuni provides a better understanding of the rationality underlying the decisions to visit the shrine. Overall, the research presented here is preliminary and should be continued to deepen the analysis and develop a more accurate model.